20 Jahre nach dem Mauerfall: Arbeitslosigkeit in ostdeutschen Regionen - Uwe Blien; Van Phan thi Hong; Klara Kaufmann; Steffen Kaimer (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2010)
– Themes of the paper are differences in unemployment rates between East and West Germany and the spatial differentiation in the East. 20 years after the fall of the Berlin Wall there is still a strong division between the economies and labour markets of Eastern and Western Germany. In the last few years, however, unemployment has been reduced especially in the East. Within Eastern Germany a strong variation of labour market situations is visible, which has been relatively stable in time. In the paper special approaches of regional economics are used to understand the situation. In addition, a spatial econometrics framework is applied.
Keywords: 330; Arbeitslosigkeit; regionale Faktoren; regionale Verteilung; IAB-Beschäftigtenstichprobe; regionale Disparität; Beschäftigungsentwicklung; Arbeitslosenquote; Regionalökonomie; Einkommenshöhe; Ostdeutschland